Role of ACE1, ACE2, and CCR5-Δ32 Polymorphisms in the Transmission of SARS-CoV-2 to Intimate Contacts - Maria Pina Dore; Alessandra Errigo; Elettra Merola; Giovanni Mario Pes (Biology)
Background. Despite the high transmissibility of SARS-CoV-2, some individuals remain uninfected despite prolonged exposure to a high viral load, suggesting the involvement of an innate resistance mechanism, possibly underpinned by the host’s genetic factors. The angiotensin-converting enzyme-1 (ACE1), ACE2, and C-C Chemokine Receptor 5 (CCR5) polymorphisms have been shown to influence susceptibility to the infection. In this study, the role of ACE1, ACE2, and CCR5 gene polymorphisms in modulating susceptibility to SARS-CoV-2 infection within the context of intimate contact was evaluated. Methods. A cohort of heterosexual couples from Northern Sardinia, characterized by a homogenous genetic background, was recruited during the initial pandemic wave (March–June 2020). In each couple, one partner (index case) tested positive for SARS-CoV-2 by at least two consecutive independent molecular tests (real-time polymerase chain reaction: RT-PCR) on nasopharyngeal swabs. Bed-sharing partners of SARS-CoV-2 positive index cases, resistant and susceptible to the infection, were genotyped for ACE1 287 bp Alu repeat insertion/deletion (I/D) polymorphism, ACE2 G8790A (rs2285666) variant, and a 32-base pair deletion (Δ32) of CCR5. Resistant and susceptible partners to the infection were compared for polymorphisms. Results. Out of 63 couples, 30 partners acquired SARS-CoV-2 infection, while 33 remained uninfected despite intimate exposure. Clinical history was minimal for current or past illnesses. SARS-CoV-2-infected index spouses and partners who acquired the infection developed a mild disease, not requiring hospitalization. The observed distribution of ACE1 I/D and ACE2 G8790A genotypes was consistent with previously reported frequencies in Sardinia and across European populations. None of the study participants carried the CCR5-Δ32 variant. No statistically significant differences (p > 0.05) in the allelic or genotypic frequencies of these polymorphisms were observed between the infected and resistant partners. Conclusions. No differences in the distribution of ACE1, ACE2, and CCR5 polymorphisms between the two groups were detected. These findings suggest that resistance is likely multifactorial, involving a complex interplay of genetic, immunological, and environmental factors.